2020
DOI: 10.3390/agronomy10050679
|View full text |Cite
|
Sign up to set email alerts
|

Wild Miscanthus Germplasm in a Drought-Affected Area: Physiology and Agronomy Appraisals

Abstract: Predictions of future climate scenarios indicate that yields from perennial biomass crops (PBCs) growing in the Mediterranean region are likely to decline due to prolonged drought. Among PBCs, Miscanthus grasses with C4 photosynthesis combine high yield potentials and water use efficiencies. However, the standard commercial clone M. x giganteus (Mxg), with minimal stomatal regulation, is too sensitive to drought for reliable yields in the Mediterranean regions. This paper screened a diverse panel of thirteen M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…It is imperative that agriculture will take these threats as opportunities, by diversifying crop options, introducing new cropping systems with locally adapted genotypes combined with sustainable agronomic practices to provide raw material for the bioeconomy and to conserve natural resources [38]. Advanced research on locally adapted plants, aimed at identifying stress-resilient traits and to breed resource-efficient and climate-resilient genotypes, will likely play a key role in strength synergies among farmers, practitioners, and industries to optimize bioeconomy value chains [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…It is imperative that agriculture will take these threats as opportunities, by diversifying crop options, introducing new cropping systems with locally adapted genotypes combined with sustainable agronomic practices to provide raw material for the bioeconomy and to conserve natural resources [38]. Advanced research on locally adapted plants, aimed at identifying stress-resilient traits and to breed resource-efficient and climate-resilient genotypes, will likely play a key role in strength synergies among farmers, practitioners, and industries to optimize bioeconomy value chains [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…This was the finding at the Chanteloup site (shallow sandy soil with a maximum soil water capacity of 149 mm and rainfall lower than 400 mm) where M. sinensis obtained higher yields than M. x giganteus. Scordia et al [37] found similar results and showed a low yielding of M. x giganteus compared to M. sinensis established in sandy soil in Italy. In a context of climate change, characterized in several regions by a higher rainfall variability, the choice of genotypes for a perennial crop should be for the most stable yields across years [37] and even better if they are high and stable.…”
Section: What Perspectives For Genotype Choice For a Given Environment Crop Management And Plant Breeding?mentioning
confidence: 61%
“…Scordia et al [37] found similar results and showed a low yielding of M. x giganteus compared to M. sinensis established in sandy soil in Italy. In a context of climate change, characterized in several regions by a higher rainfall variability, the choice of genotypes for a perennial crop should be for the most stable yields across years [37] and even better if they are high and stable. For this purpose, on sites with low water availability and sandy soils, M. sinensis would be a better choice than M. x giganteus.…”
Section: What Perspectives For Genotype Choice For a Given Environment Crop Management And Plant Breeding?mentioning
confidence: 61%
See 1 more Smart Citation
“…Miscanthus demonstrates stand and harvest longevity exceeding 15 years (Clifton‐Brown et al., 2019) and, once established, expresses considerable drought (Scordia et al., 2020) and flood (Kam et al., 2020) tolerance with low to zero requirements for herbicide treatments and fertilization (Cosentino et al., 2007). The commercially dominant triploid Miscanthus x giganteus ( Mxg ) is a natural interspecific hybrid between diploid Miscanthus sinensis (2n = 2x = 38) and allotetraploid Miscanthus sacchariflorus (2n = 4x = 76; Greef & Deuter, 1993; Linde‐Laursen, 1993; Rayburn et al., 2009).…”
Section: Introductionmentioning
confidence: 99%